A corpus-driven analysis of male and female weblog users in an ESL context / Huang Wen Jie - Huang, Wen Jie (2015)
Weblogs ushered a new epoch for Malaysian ESL learners ever since its first entry to Malaysia in 1998 (Hopkins, 2010). Since then, scholars in the field of English as a Second Language (ESL) have paid considerable attention to blogging, especially those who teach writing courses (Mah and Er, 2009; Mah and Liaw, 2011; Gedera, 2012; Kaur, Ganapathy, and Sidhu, 2012; Yunus, Kiing, and Salehi, 2013; Ubaidullah, Mahadi, and Ching, 2013). However, little research has been undertaken from a sociolinguistic perspective, let alone gender-oriented to analyse adults’ weblogs. To fill the gap and promote online communication in an ESL community, the present study uses a corpus-driven approach and via a corpus tool, namely, Wmatrix (Rayson, 2013) to tag the key semantic domains (primary) and parts of speech (auxiliary) in 200 ESL weblogs produced by 100 Malaysian females and 100 males from http://www.blogmalaysia.com/. Quantitative results reveal gender differences identified by the log-likelihood value in females’ and males’ use of key semantic domains and parts of speech. Findings reveal that certain semantic domains and parts of speech are more significant and predominantly found in the female weblogs compared to the males. The findings are also attributed to socio-cultural contexts. Future research can be conducted with other groups of bloggers and a larger corpus is also recommended. Keywords: Corpus linguistics, semantic domain, part of speech, weblog, gender, Wmatrix